Assessment of Intellectual Functioning among Children with Neurodevelopmental Disorders: Challenges and Implications Beyond the Clinical Practice - Hristova, Mihaela; Manolova, Harieta; Staykova, Svetla; Markova, G (Journal of Intellectual Disability - Diagnosis and Treatment, 2018)
Early and precise identification of neurodevelopmental disorders together with provision of adequate and timely interventions remain increasingly important tasks for multidisciplinary clinical teams. А central component in this process of comprehensive clinical evaluation is the assessment of children’s intellectual functioning. Intelligence test results represent a central component in the decision making process of determining a child’s future in terms of: qualification for special education, access to social welfare support, placement in therapeutic programs, etc. Clinical results yielded through the application of standardized intelligence assessment instruments (WISC, K-ABC, RPM), and especially the overall quantitative measure of cognitive ability (IQ) have become a central, and sometimes the only measure taken into consideration when determining a child’s level of functioning. Together with some distinct benefits, this practice places many children at risk of being underestimated and calls for revision and modification of standard assessment procedures. In line with these considerations, authors raise for discussion traditional approaches to diagnostics of intellectual functioning, highlighting some challenges, emerging from the constitutive particularities in the cognitive functioning of children with neurodevelopmental disorders. An attempt for identifying areas for further improvement alongside with research-informed recommendations for a contemporary, individualized and sensitive to the specifications of children with neurodevelopmental disorders assessment practice are outlined at the end of this paper. According to the authors’ opinion, exploration of the topic provides an important opportunity to advance the understanding of clinicians, primary healthcare professionals, educators and other professionals involved in supporting children with developmental deficits.